Fire Behavior of the Assembled Monolithic Hollow-Ribbed Slabs - B. Li; Y. Q. Lin; H. L. Zhang; M. J. Ma (Advances in Civil Engineering, 2019)
This paper presents the results from the furnace tests conducted on two assembled monolithic hollow-ribbed (AMH) slabs consisting of the open box and the covered box, respectively. Detailed experimental data in the form of describing slab cracking or spalling, furnace temperatures, temperature distributions, and vertical deflections are presented. Comparison of the results from the two fire tests indicates that the covered box shows better fire resistance compared to the open box; thus, the covered box is recommended to adopt in structural fire-resistant design. However, they are both prone to cracking or spalling at their bottom surfaces during the fire tests, so the AMH slab still needs further optimum design to meet its requirements of fire resistance and service function. In addition, the sealing quality of congruent boxes also has a great influence on the fire resistance of the AMH slab.